Transgenerational transduction of MPTP-induced alterations in a Parkinson's disease mouse model - Alvarez-Fischer, D.; Vernik, T.; Vulinovic, F.; Herrmann, A.; Westenberger, A.; Klein, C. (Parkinsonism & related disorders, 2020)
Susceptibility to Parkinson's disease (PD) increases more than threefold in first-degree relatives of PD patients. Using a mouse model, we investigated in a proof-of-principle approach whether toxin exposure of F0 affects the F1 generation. We provide first evidence that disturbance of the nigrostriatal pathway can be transferred to the next generation.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Epigenetic; Neurodegeneration